2021
DOI: 10.1128/jvi.02107-20
|View full text |Cite
|
Sign up to set email alerts
|

A Gammacoronavirus, Avian Infectious Bronchitis Virus, and an Alphacoronavirus, Porcine Epidemic Diarrhea Virus, Exploit a Cell Survival Strategy by Upregulating cFOS To Promote Virus Replication

Abstract: Coronaviruses have evolved a variety of strategies to optimize cellular microenvironment for efficient replication. In this study, we report the induction of AP-1 transcription factors by coronavirus infection based on genome-wide analyses of differentially expressed genes in cells infected with avian coronavirus infectious bronchitis virus (IBV). Most members of the AP-1 transcription factors were subsequently found to be upregulated during the course of IBV and porcine epidemic diarrhea virus (PEDV) infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…The functional efficacy of cFOS is mainly driven by de novo protein synthesis, whereas cJUN is mainly activated by phosphorylation at the N-terminal Ser63 and Ser73 residues by JNK [60]. Consistently, our recent study has shown that in IBVinduced H1299 cells, cFOS mRNA was induced by~500-fold while cJUN mRNA was induced by~40-fold [45]. In addition, the basal level of cFOS protein was not detectable in the uninfected cells, but it rose to very high levels at the peak of IBV infection [45].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The functional efficacy of cFOS is mainly driven by de novo protein synthesis, whereas cJUN is mainly activated by phosphorylation at the N-terminal Ser63 and Ser73 residues by JNK [60]. Consistently, our recent study has shown that in IBVinduced H1299 cells, cFOS mRNA was induced by~500-fold while cJUN mRNA was induced by~40-fold [45]. In addition, the basal level of cFOS protein was not detectable in the uninfected cells, but it rose to very high levels at the peak of IBV infection [45].…”
Section: Discussionsupporting
confidence: 78%
“…Use of a specific cFOS inhibitor, such as T-5224, a rationally designed small molecule that inhibits the DNA binding activity of cFOS/cJUN, would be of help in exploring this possibility further. In fact, when H1299 cells were treated with T-5224 at 12.5 µM in a previous study, IBV replication was not affected, but IBV-induced IL-8 expression was significantly reduced compared with the solvent-treated control [ 45 ]. It suggests that the DNA binding activity of cFOS is indeed required for IBV-induced IL-8 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The upstream MAPK kinases and particularly MKK7 were shown to be responsible for JNK activation which served as a pro-apoptotic protein modulating the anti-apoptotic protein Bcl2; yet the pro-apoptotic activities of JNK was mediated independent of c-Jun which probably promotes cell survival [105]. A recent study revealed that ERK1/2 kinases activate cFOS which in turn suppresses apoptosis of the infected cells at early to intermediate phases of the IBV infection cycle in favor of viral replication [106].…”
Section: Gammacoronavirus Avian Infectious Bronchitis Virus (Ibv)mentioning
confidence: 99%